A CASE OF NON-OCCLUSIVE MESENTERIC INFARCTION FOLLOWING OPERATION FOR A COLONIC CANCER - SATOMI, Takashi; MASUTANI, Seizo; ISHIDA, Hideyuki; TATSUTA, Masayuki; HANAI, Jun; KAWASAKI, Takatoshi (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 1998)
A 58-year-old man was operated for a cancer of the ascending colon at the hospital. On the first day after the operation the patient's condition was well. But from the morning of the second day he felt an abdominal pain and abdominal fullness. Then anal bleeding occurred in the afternoon, leading to heart failure even though the bleeding was minimal. Eventually respiratory insufficiency progressed and he died of multiple organ failure on the third day after operation. Autopsy was conducted immediately and we found necrosis involving from the ileum to half of the jejunum. There was no anastomotic leakage at the ileo-colostomy nor intestinal obstruction. We could not find any occlusion and thrombosis in the superior mesenteric artery and vein. From these findings, the case was diagnosed as non-occlusive mesenteric infarction (NOMI). The prognosis of NOMI is very poor, because it presents difficulty in early diagnosis. Although it is vey common for the patients after abdominal surgery to complain abdominal pain and fullness, we must keep this fatal NOMI in mind as a possible rare complication after abdominal surgery.